The Effect of Bokashi from Goat Manure and Human Urine on the Growth of Lettuce (Lactuca sativa L) in Deep Flow Technique (DFT) System - Dedi, Ronaldus; Situmeang, Doli; Ricky, Donn Richard (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
In the pursuit of innovative agricultural practices, the Deep Flow Technique (DFT) hydroponic system has gained popularity to meet the increasing demand for vegetables, such as lettuce. However, finding effective organic fertilizers remains a challenge. This study aimed to investigate the impact of using bokashi from goat manure and human urine on lettuce growth within the DFT system, comparing it to the commonly used AB Mix fertilizer. The experiment observed growth parameters, including root length, number of leaflets, and leaf width, for a period of 28 days. The results indicated that the AB Mix fertilizer yielded the best growth, followed by a combination of goat manure bokashi and human urine, whereas human urine alone resulted in the lowest growth. Statistical analysis confirmed the significant influence of the fertilizer treatments on plant growth. These findings suggest that while AB Mix fertilizer is the optimal choice, the combination of goat manure bokashi and human urine proves to be a viable alternative for organic fertilizer.